Targeted Delivery of GP5 Antigen of PRRSV to M Cells Enhances the Antigen-Specific Systemic and Mucosal Immune Responses - Du, Luping; Yu, Zhengyu; Pang, Fengjiao; Xu, Xiangwei; Mao, Aihua; Yuan, Wanzhe; He, Kongwang; Li, Bin (Frontiers in Cellular and Infection Microbiology, 2018)
Efficient delivery of antigens through oral immunization is a first and critical step for successful induction of mucosal immunity, which can provide protection against pathogens invading the mucosa. Membranous/microfold cells (M cells) within the mucosa can transcytose internalised antigen without degradation and thus play an important role in initiating antigen-specific mucosal immune responses through inducing secretory IgA production. In this research, we modified poly (D, L-lactide-co-glycolide) (PLGA) nanoparticles (NPs) with Ulex europaeus agglutinin 1 (UEA-1) and successfully prepared an oral vaccine delivery system, UEA-1/PLGA NPs. PLGA NPs were prepared using a standard double emulsion solvent evaporation technique, which can protect the entrapped PRRSV DNA vaccine (pcDNA3.1-SynORF5 (synthetic ORF5)) or subunit vaccine ORF5-encoded glycoprotein (GP5) from exposure to the gastrointestinal (GI) tract and release the plasmids in a controlled manner. With UEA-1 modification, the UEA-1/PLGA NPs can be effectively transported by M-cells. We investigated immune response induced by UEA-1/PLGA-SynORF5 or UEA-1/PLGA-GP5 following inoculation in mice and piglets. Compared with PLGA-SynORF5 or PLGA-GP5 NPs, UEA-1/PLGA-SynORF5 or UEA-1/PLGA-GP5 NPs stimulated significantly increased serum IgG levels and augmented intestinal IgA levels in mice and piglets (P<0.05). Our findings indicate UEA-1/PLGA NPs can be applied as a promising and universally robust oral vaccine delivery system.